Wet oxidation of sewage sludge from municipal and industrial WWTPs. Issue 6 (1st February 2016) - Bertanza, Giorgio; Galessi, Raniero; Menoni, Laura; Zanaboni, Sabrina
Abstract: In the last years, sewage sludge management turned out to be a topic of great interest due to the increasing sludge production and the high cost of sludge treatment and disposal. In this context, several methods are being studied for sewage sludge minimization: among them, wet oxidation (WO) was proposed as an effective hydrothermal oxidation based technology. The aim of this work, carried out within the European project "ROUTES, " was the assessment of the influence of sludge composition on process performance: for this purpose, seven different types of sewage sludge were submitted to WO tests at lab scale. Moreover, each operating condition (temperature, reaction time, and initial oxygen pressure) was varied so as to highlight the effect of process parameters on oxidation efficiency; this was essentially evaluated in terms of chemical oxygen demand (COD), volatile suspended solid (VSS) and total suspended solid (TSS) reduction. COD and VSS abatement varied in the ranges 44–85%, 71–99% depending on reaction time (15–120 min) and 22–79%, 54–99% as a function of temperature (200–250°C), respectively. Furthermore, by comparing WO tests results of the seven types of sludge obtained under the same treatment conditions (temperature = 250°C and reaction time = 60 min), it was highlighted that VSS and COD removal efficiency can be correlated to the initial VSS/TSS ratio.